Neurosurgery service development prospective after medical service reforms in Ukraine - Polishchuk, Mykola (Ukrainian Neurosurgical Journal, 2016)
There are a lot of neurosurgical beds and neurosurgeons in Ukraine. In many cities neurosurgical service provide a medical care for patients mainly with mild to moderate degree of TBI. Surgical activity is very low. The number of operations per neurosurgeon is nearly 50, and without TBI patients — 38 per year. This raises o lot of questions and concerns about the competence of professionals. There are unreasonably large number of neurosurgeons and neurosurgical beds in the Kyiv also. We can conclude that at least 50% of patients in some offices are hospitalized without indications. In case of implementing medical staff salary based on payment for patient’s treatment number of neurosurgical beds and neurosurgeons can be reduced. Ukrainian Association of Neurosurgeons and regional associations should inspect the service and every neurosurgeon and identify the way for optimization and be ready to work in new reformed medicine.